Aeromonas spp. in drinking water and food: Occurrence, virulence potential and antimicrobial resistance - Carusi, Juliana; Kabuki, Dirce Yorika; de Seixas Pereira, Pedro Marques [UNESP]; Cabral, Lucélia [UNESP] (Elsevier, 2024)
Aeromonas sp. is a Gram-negative, non-spore-forming, rod-shaped, oxidase-positive, facultative anaerobic bacterium and a natural contaminant found in aquatic environments. Some species can invade, colonize, and damage host cells due to the presence of virulence factors, such as flagella, elastase, hemolysins, aerolysins, adhesins, enterotoxins, phospholipases and lipases, that lead to pathogenic activities. Consequently, can cause many health disorders that range from gastrointestinal problems, enteric infections, and ulcers to hemorrhagic septicemia. Aeromonas has been isolated and identified from a variety of sources, including drinking water and ready-to-eat foods (fish, meat, fresh vegetables, dairy products, and others). Some species of this opportunistic pathogen are resistant to several commercial antibiotics, including some used as a last resort for treatment, which represents a major challenge in the clinical segment. Antimicrobial resistance can be attributed to the indiscriminate use of antibiotics by society in aquaculture and horticulture. In addition, antibiotic resistance is attributed to plasmid transfer between microorganisms and horizontal gene transfer. This review aimed to (i) verify the occurrence of Aeromonas species in water and food intended for human consumption; (ii) identify the methods used to detect Aeromonas species; (iii) report on the virulence genes carried by different species; and (iv) report on the antimicrobial resistance of this genus in the last 5 years of research. Additionally, we present the existence of Aeromonas spp. resistant to antimicrobials in food and drinking water represents a potential threat to public health.
Keywords: Aeromonas; Antimicrobial resistance; Dependent and independent cultivation methods; Drinking water; Food; Virulence factors